Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Matematika SDN 13 Saruaso Timur - Ismarsuti,; Nur Rezki, Maulia; Yetri, Peja (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Curriculum administration is an essential element in supporting the quality of learning in elementary schools. This literature review explores various approaches in curriculum administration, including traditional methods such as academic and administrative supervision, as well as modern innovations through technology integration. The findings of the study indicate that traditional approaches offer stability and structure, while technological innovations provide greater efficiency and flexibility. The success of curriculum administration is influenced by the leadership of the school principal, a collaborative school culture, and the active involvement of teachers. Challenges such as limited technological infrastructure and adaptation to changes in educational policies require solutions such as technology training, increased investment in digital devices, and the development of a work culture that supports collaboration. By combining traditional and innovative approaches, curriculum administration can be more responsive to the needs of students and the community. Through this analysis, the review contributes significantly to the understanding of the role of curriculum administration in creating quality learning and supporting the achievement of national educational goals.